Quantitative Research on Water Security in Zhengzhou City Based on SD-BC Theory - SONG Sunjuan; MAO Haolin; HAN Yuping; DOU Ming; ZHANG Huaqiao (Renmin Zhujiang)
With the rapid development of economy and society, the contradiction between supply anddemand of water resources in many cities has become more and more acute, which leads to severewater security hazards.Taking Zhengzhou city as the research object, this paper carries out aquantitative study on water security in Zhengzhou as follows. First, based on the analysis of theinfluencing factors of urban water security, it describes the water security system by organicallylinking the subsystems of society, economy and ecological environment through human activitiessuch as supply, use, consumption and drainage, so as to construct the framework of urban watersecurity system.Secondly, it establishes a SD-BC simulation model of water security system coupledwith water resources system, socio-economic system and ecological environment system by combiningsystem dynamic (SD) method with backcasting (BC).Finally, according to the water resourcesconditions and urban social and economic development of Zhengzhou city, it takes 2014 as the baseyear to simulate and predict the water security system from 2015 to 2025, evaluate the watersecurity degree of Zhengzhou city, and put forward suggestions on water security measures, whichprovide theoretical basis for optimizing the allocation of water resources and ensuring urbanwater security.